Acute weight cycling and hydration status in elite kickboxers: a repeated-measures field study - Ceylan, B.; Taskin, H. B.; Sarikaya, U.; Pekel, H. A.; Sabirli, T. N. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Objective This study aimed to monitor acute changes in body weight and hydration status—measured via urine-specific gravity (USG) and urine color (UC)—in elite-level kickboxers during a real-world competitive environment. The research sought to provide critical insights into current weight-management practices and the prevalence of hypohydration during the pre-competition period.